This land is your land [videorecording (DVD)] : the folk years. - Collins, Judy, 1939-; Yarbrough, Glenn, 1930-2016; McGuire, Barry, 1935-; McGuinn, Roger; Sparks, Randy (RHINO, 2003)
Features the biggest names in folk music. Join The Smothers Brothers and Judy Collins as they guide performances by The Kingston Trio, The Highwaymen, Roger McGuinn, and many more.